2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--30760
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from a Chemical Engineering REU: The Importance of Training Graduate Students Who are Supervising REU Students

Abstract: Penn State and is currently a doctoral candidate in the same program. The primary focus of her research concerns assessing the response structure of test scores using item response theory methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…REU programs provide participants with valuable experiences that supplement their traditional engineering coursework [5]. REU programs provide students with opportunities to gain real-world, hands-on experiences working in labs with other researchers and help students to develop research skills and a deeper understanding of the research process.…”
Section: Undergraduate Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…REU programs provide participants with valuable experiences that supplement their traditional engineering coursework [5]. REU programs provide students with opportunities to gain real-world, hands-on experiences working in labs with other researchers and help students to develop research skills and a deeper understanding of the research process.…”
Section: Undergraduate Researchmentioning
confidence: 99%
“…Research on sense of belonging has shown that women who experience a high sense of belonging are more likely to persist through their undergraduate academic programs [4]. Productive research experiences for undergraduates, such as the REU program, can successfully promote sense of belonging, retention, and persistence for students in engineering majors [5]. Therefore, to examine women students' sense of belonging in the 10week Summer REU program, belongingness of undergraduate women and men participants were measured and compared.…”
Section: Introductionmentioning
confidence: 99%
“…Most mentoring initiatives between graduate and undergraduate Science, Technology, Engineering, and Mathematics (STEM) students revolve around research activities such as those that take place in Research Experiences for Undergraduates (REUs), where graduate students run summer research programs for undergraduates that faculty advisors have developed [36]. Few mentoring models between graduate and undergraduate students exist in design courses [37] and none were found related to ECD.…”
Section: Extension Of Graduate Research Into Courses and Projectsmentioning
confidence: 99%